The cycle of solitude and avoidance: a daily life evaluation of the relationship between internet addiction and symptoms of social anxiety - Hernández, Cristóbal; Ferrada, Martín; Ciarrochi, Joseph; Quevedo, Sergio; Garcés, José Antonio; Hansen, Raimundo; Sahdra, Baljinder (Frontiers in Psychology, 2024)
A consistent association has been observed between internet addiction and symptoms of social anxiety. However, there is a lack of empirical research that delves into potential explanations for this relationship and its directionality, making it difficult to translate findings into development of interventions for social anxiety that account for technology-related behaviors. The present study aimed to evaluate the longitudinal dynamics between internet addiction, symptoms of social anxiety, avoidance of social interactions, and using the internet to cope with loneliness. By means of an ecological momentary assessment study, we evaluated a sample of 122 young adults from Chile using intensive self-report measurements five times a day, for a period of 10 days. Using mixed-effects models, we examined the directionality between internet addiction and symptoms of social anxiety, together with an explanation of their relationship. Results indicate that internet addiction antecedes symptoms of social anxiety; however, the reverse relationship was not observed. Furthermore, instances where individuals avoided social interactions or used the internet to cope with loneliness were predictive of later increases in levels of internet addiction, suggesting a vicious cycle. Significant heterogeneity was observed in these effects, highlighting the need for a more personalized approach when including technology-related behaviors in social anxiety interventions. Theoretical and clinical implications are discussed.